1999
DOI: 10.1242/dev.126.3.469
|View full text |Cite
|
Sign up to set email alerts
|

The PINHEAD/ZWILLE gene acts pleiotropically in Arabidopsis development and has overlapping functions with the ARGONAUTE1 gene

Abstract: Several lines of evidence indicate that the adaxial leaf domain possesses a unique competence to form shoot apical meristems. Factors required for this competence are expected to cause a defect in shoot apical meristem formation when inactivated and to be expressed or active preferentially in the adaxial leaf domain. PINHEAD, a member of a family of proteins that includes the translation factor eIF2C, is required for reliable formation of primary and axillary shoot apical meristems. In addition to high-level e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 430 publications
(20 citation statements)
references
References 16 publications
0
18
1
1
Order By: Relevance
“…Observations of acropetal procambial strand development appear contradictory to this idea and could be interpreted as lending support to the opposing procambial strand hypothesis that states that the acropetal formation of leaf trace procambium provides a positional signal for leaf initiation (Larson, 1983). Although we did not observe precocious procambial strands in our study, an earlier study of the function of the PINHEAD gene in Arabidopsis (Lynn et al, 1999) showed strong expression in a restricted region of cells corresponding to the location of a leaf trace procambial strand that anticipated leaf formation by at least one plastochron (in comparison, ATHB-8::GUS expression was not detected before leaf formation). These two perspectives might not be mutually exclusive, however, since basipetally-moving positional signals from a primordium or its presumptive site might interact with signals moving acropetally from antecedent vasculature to establish a prepattern in predictable positions (Larson, 1983;Kirchoff, 1984;Berleth et al, 2000a,b).…”
Section: Discussioncontrasting
confidence: 90%
“…Observations of acropetal procambial strand development appear contradictory to this idea and could be interpreted as lending support to the opposing procambial strand hypothesis that states that the acropetal formation of leaf trace procambium provides a positional signal for leaf initiation (Larson, 1983). Although we did not observe precocious procambial strands in our study, an earlier study of the function of the PINHEAD gene in Arabidopsis (Lynn et al, 1999) showed strong expression in a restricted region of cells corresponding to the location of a leaf trace procambial strand that anticipated leaf formation by at least one plastochron (in comparison, ATHB-8::GUS expression was not detected before leaf formation). These two perspectives might not be mutually exclusive, however, since basipetally-moving positional signals from a primordium or its presumptive site might interact with signals moving acropetally from antecedent vasculature to establish a prepattern in predictable positions (Larson, 1983;Kirchoff, 1984;Berleth et al, 2000a,b).…”
Section: Discussioncontrasting
confidence: 90%
“…The spatial distribution of HD-ZIPIII proteins may also rely on miRNA binding by Argonaute proteins (AGOs). In Arabidopsis, the adaxial-and SAM-expressed AGO10, also known as PINHEAD/ZWILLE (Moussian et al, 1998;Lynn et al, 1999), specifically sequesters and degrades miR165/166 and thus indirectly upregulates HD-ZIPIII expression (Liu et al, 2009;Ji et al, 2011;Zhu et al, 2011;Zhou et al, 2015). These multidimensional bidirectional repressive circuits may lead to robust adaxial domain identity.…”
Section: Maintenance Of Adaxial-abaxial Polaritymentioning
confidence: 99%
“…For example, the maize tangled1 and warty-1 mutants both show cell division defects while the affected cells, and therefore tissues and organs, differentiate relatively normally [ 50 , 59 , 60 ]. However, and relating directly to the severity of the expressed developmental phenotype, assignment of a specific function to a gene in one or both of these processes can prove challenging to interpret when differentiation is altered sufficiently to cause major changes to the arrangement of tissues in an organ, such as the challenges posed with assigning primary function to a gene in mutant plant lines such as the phan mutant of Antirrhinum [ 32 , 46 ] or the phabulosa and pinhead / zwille mutants of Arabidopsis [ 61 , 62 ]. In all three mutant plant lines, the development of the different cell types which comprise the tissue along the dorsoventral axis is affected by loss of function of each of these genes leading to gross changes to overall leaf size and shape, as well as to also drastically alter the arrangement of each tissue of the leaves or leaf-like structures which form in the phan , phabulosa and pinhead / zwille mutant backgrounds [ 32 , 46 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%